2015
DOI: 10.1007/s10508-014-0471-3
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Romantic Attraction and Conflict Resolution in Predicting Shorter and Longer Relationship Maintenance Among Adolescents

Abstract: This study examined the role of romantic attraction and conflict resolution patterns in shorter and longer relationship maintenance among adolescent couples. Data were used from 55 couples aged 15-18 years. Partners completed the Romantic Attraction scale and were observed negotiating a disagreement. Three and 6 months later, they were asked to report whether they were still together. Findings indicated that partners' romantic attraction and the tendency to minimize disagreements during interaction predicted s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…These strategies can take the form of a lack of clarification of the expectations and can threaten the relationship. The affection for the partner may also encourage youth to withdraw from disagreements, rather than harming the couple's harmony (Appel & Shulman, ). Avoidance remains the preferred option for the dyads with entangled interactions, as attempts to resolve disagreements are likely to create more tension in the relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These strategies can take the form of a lack of clarification of the expectations and can threaten the relationship. The affection for the partner may also encourage youth to withdraw from disagreements, rather than harming the couple's harmony (Appel & Shulman, ). Avoidance remains the preferred option for the dyads with entangled interactions, as attempts to resolve disagreements are likely to create more tension in the relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it would be easier for youth to resolve their romantic conflicts during late adolescence. Studies also showed that positive conflict resolution strategies contribute to the ability to maintain romantic relationships and act as a protective factor for dating victimization (Appel & Shulman, ).…”
Section: Conflicts and Conflict Resolution Strategies In Romantic Relmentioning
confidence: 99%
“…Passionate love and romantic attraction share similar characteristics; they both induce increased physiological arousal, sexual desire, desire for union, and attention focused on the partner (Fisher, 2004;Fisher, Aron, Mashek, Li, & Brown, 2002;Berscheid, 2010). Additionally, research has shown a positive correlation between passionate love, romantic attraction, and sexual desire (Appel & Shmuel, 2015;Diamond, 2004;Gonzaga, Turner, Keltner, Campos, & Altemus, 2006). More specifically, research suggests that passionate love, romantic attraction, and sexual desire serve to assist in the initiation of relationships, and face a time course constraint, such that decreases in these constructs occur over time as the relationship becomes more committed and established (see Gonzaga et al, 2006).…”
Section: Studymentioning
confidence: 99%
“…Handling conflicts constructively is essential for relational need fulfillment. Relationship education programs should address risk factors that might impel relationship aggression, which is more common during this time (Appel & Shulman, 2015; Fischer et al, 2004; Johnson et al, 2015) as well as factors that inhibit aggression. Our findings suggest that reflecting back on past conflicts related to unmet needs is a task that involves the management of anger associated with more relationship aggression.…”
Section: Discussionmentioning
confidence: 99%